Research on factors affecting serial entrepreneurial intention: An interpretive structure model - Bai, Xiuwei; Cheng, Dejun; Chen, Yuting (Frontiers in Psychology, 2022)
Serial entrepreneurship is a very common phenomenon in the world. Research on serial entrepreneurs is the core of understanding entrepreneurship and entrepreneurs, such as, why entrepreneurs insist on starting businesses many times? What affects the sustainability of entrepreneurship? Based on the interpretive structure model of systems engineering, this study constructs a hierarchical model of the factors affecting serial entrepreneurial intention, which proposed the basic conditions, key factors, and paths affecting serial entrepreneurial intention. Based on this, the hierarchical model of factors affecting serial entrepreneurial intention is also tested through a typical serial entrepreneurial case. The results show that: (1) there are 16 factors affecting serial entrepreneurial intention, and each factor plays a role at a specific level; (2) entrepreneurial expectations and identification and evaluation of opportunities are the key factors affecting serial entrepreneurial intention. We can improve the ability of the identification and evaluation of opportunities through entrepreneurial failure learning, and form reasonable entrepreneurial expectations; (3) entrepreneurial cognitive schema and behavioral addiction tendency directly affect entrepreneurs’ identification and evaluation of opportunities; (4) demographic factors, financial conditions, environmental conditions, and entrepreneurial experience are the basic conditions that affect serial entrepreneurial intention indirectly through emotional perception and motivation factors.